オーロラ デンシ カンソク シリョウ ショリ a. ニュウシャ リュウシ ト オーロラ ダイ 1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 和田, 雅美; ワダ, マサミ; 奥谷, 晶子; オクタニ, ショウコ; 今井, 喬; イマイ, タカシ; 竹内, 一; タケウチ, ハジメ; 小玉, 正弘; コダマ, マサヒロ; WADA, Masami; OKUTANI, Shoko; et al. (国立極地研究所, 1979)
P(論文) デジタルデータをセミアナログ的に伝送して得た磁気テープ記録から,各電子検出器の計数率をロケットのスピン,プレセッションを経て,ピッチ角分布にしていく資料処理の過程を示す. By means of semi-analogue recording of the magnetic tape which was obtained by the Antarctic rocket experiments in 1967-77, details of data processing for deducing the pitch angle distribution of auroral electrons from the observed electron counting rates are described. In this way, a viewing direction of the detector is taken into account against both the spinning and precession motions of rocket. departmental bulletin paper